2021
DOI: 10.1111/sum.12760
|View full text |Cite
|
Sign up to set email alerts
|

Soil greenhouse gas emissions, organic carbon and crop yield following pinewood biochar and biochar–manure applications at eroded and depositional landscape positions: A field trial in South Dakota, USA

Abstract: Soil amendments can help reduce greenhouse gas (GHG) emissions and increase soil organic carbon (SOC) and crop yield. However, most biochar studies have been conducted on single soil type under controlled conditions. To address this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…These differences may be because of the difference in soil types; the soil in our research was a Haplic Phaeozem (FAO, 1988), while the soil in the research conducted by Liu, Qi, et al (2017) was a Haplic Kastanozem (FAO, 1988). Abagandura et al (2022) also found that the effects of biochar on GHG emissions changed among soils with different soil textures.…”
Section: Discussionmentioning
confidence: 97%
“…These differences may be because of the difference in soil types; the soil in our research was a Haplic Phaeozem (FAO, 1988), while the soil in the research conducted by Liu, Qi, et al (2017) was a Haplic Kastanozem (FAO, 1988). Abagandura et al (2022) also found that the effects of biochar on GHG emissions changed among soils with different soil textures.…”
Section: Discussionmentioning
confidence: 97%
“…Soil represents the largest terrestrial carbon pool and holds much promise in regulating global climate (Gherardi & Sala, 2020; Hein et al, 2020; Walker et al, 2022). Depending on landscape position and soil texture, soil amendment such as biochar can be used to suppress GHG emission (Abagandura et al, 2022). The use of organic fertilizer can mitigate N 2 O emission in comparison with inorganic fertilizer (Chirinda et al, 2021; Lawrence et al, 2021).…”
Section: Climate Change Adaptation and Climate Mitigationmentioning
confidence: 99%
“…Application of organic amendments serves as a promising strategy for risk mitigation of NPs with multiple processes and mechanisms. First of all, organic amendments (e.g., compost, manure and biochar) applied to the soil increase the SOM pool (Abagandura et al, 2022 ; Armolaitis et al, 2022 ; de Figueiredo et al, 2021 ; Dong et al, 2022 ), which may reduce NP mobility via enhanced eco‐corona formation (Figure 6 ). Secondly, these amendments directly immobilize NP via heteroaggregation or adsorption (Abdoul Magid et al, 2021 ; Ayaz et al, 2022 ; Tong et al, 2020 ; L. Wang et al, 2022 ).…”
Section: Implications For Risk Mitigationmentioning
confidence: 99%